Lessons Learned from Official Airline Reports of Onboard Fumes and Smoke - Judith T. L. Anderson (Aerospace)
The author reviewed and classified maintenance reports that cited smoke, odor, or fumes (SOFs) that US airlines sent to the FAA over four years between 2018 and 2023. The US fleet composition was also calculated to put the number of SOF reports on each aircraft type in perspective. “Fume events” (engine oil or hydraulic fluid) were the most common type of onboard SOFs reported by US airlines (43%), followed by electrical (20%), and fans (6.1%). During these years, A320fam aircraft made up 20% of the US fleet but 80% of the reported fume events. Conversely, B737fam aircraft made up 27% of the US fleet but only 3.0% of the reported fume events. Aircraft design features, airline reporting practices, and maintenance procedures that may contribute to these differences were reviewed. Pilots were most likely to document a fume event during descent (47%) and takeoff/climb (19%). The A320fam, MD80fam, A330, and ERJ140-145 aircraft were over-represented in other types of SOFs reports. Airline narratives show that the APU can be the primary source of oil/hydraulic fumes, even when it is not operating. Additionally, failure to find the source of fumes, rectify it, and clean any secondary sources of fumes can cause repeat events.